(untitled) (Journal of International Studies, 2023)
This study focused on water management and control in Malaya, particularly the establishment of a ‘colonial hydrology’ in Perlis from 1909 to 1950. The study analysed water policies, management techniques, and the social and economic aspects of the local population and the global market, using archival data. This study has also highlighted the intersection between natural resources, political power, and global economic trends from an international studies perspective. The control over water resources allowed the British colonial government to strengthen its position in the global market, but this resulted in adverse effects on the environment and social justice, especially for the local population. The study has argued that sustainable and equitable approaches to resource management are needed to promote sustainable development and combat global environmental challenges. The findings of this research can inform policymakers about the importance of incorporating environmental and social justice considerations in policymaking, especially with regard to natural resource management. Overall, this study adds valuable insights to the field of international studies by highlighting how the exploitation of natural resources can have far-reaching effects, both locally and globally, thereby emphasising the need for interdisciplinary and inclusive approaches to addressing resource management issues.